Alcohol consumption during pregnancy by women from southern Brazil: a cross-sectional study - Zottis, Laira Francielle Ferreira; Souza, Mateus Arenhardt de; Hartmann, Jéssica Karine; Gama, Thiago Kenji Kurogi; Rizental, Laís Borges; Maciel, Anita Machado; Gresele, Merialine; Rosa, Ernani Bohrer da; Nunes, Maurício Rouvel; Rocha, Juliana Trevisan da; Telles, Jorge Alberto Bianchi; Cunha, André Campos da; et al. (São Paulo Medical Journal, 2025)
BACKGROUND: Some maternal characteristics are related to alcohol intake during pregnancy, which irreversibly compromises the maternal-fetal binomial integrity. OBJECTIVES: To identify the frequency, impact, and factors associated with alcohol consumption during pregnancy. DESIGN AND SETTING: A cross-sectional study was performed at the Hospital Materno Infantil Presidente Vargas (HMIPV) in Porto Alegre/RS between March and December 2016. METHODS: A structured questionnaire was administered along with a medical records review. They refer to the maternal sociodemographic and gestational status, alcohol consumption patterns, and characteristics of the fetus/newborn. In the statistical analysis, P values < 0.05 were considered significant. RESULTS: The frequency of alcohol intake was 37.3%; this was characterized by the consumption of fermented beverages (89.3%), especially during the first trimester (79.6%). Risky consumption (high and/or early) occurred for 30.2% of participants. Risk factors associated with maternal alcohol consumption during pregnancy were tobacco use (P < 0.001) and abortion attempt (P = 0.023). Living with a partner (P = 0.002) and planning pregnancy (P = 0.009) were protective factors. Risky consumption was related to all of the aforementioned variables as well as threatened abortion (P = 0.023). CONCLUSIONS: Alcohol intake during pregnancy is common and affects nearly one-third of pregnant women. Knowledge of the population at risk and protective factors is essential for the development of campaigns that seek to reduce consumption and, therefore, its consequences for the mother and fetus.